Experimental and theoretical analysis of H and Ti co-doped ZnO transparent conductive films. Issue 7 (May 2017) - Wang, Yanfeng; Song, Jianmin; Zheng, Wei; Pei, Hailin; Wang, Xiaohe; Wang, Dan; Niu, Guozhen; Song, Qinggong; Yang, Fu; Nan, Jingyu
Abstract: Ti-doped ZnO (TZO) films were grown by radio frequency (RF) magnetron sputtering using a Ti-doped ZnO ceramic target in an Ar+H2 atmosphere at room temperature. Both the experimental and theoretical methods were employed to investigate the effect of H in TZO films. As the H2 flow rate increased, the surface morphology changed from pyramid-like features to a crater-like topography and the root-mean-square (RMS) roughness increased. The crystal quality was found to deteriorate at first but subsequently improved at an optimum doping ratio. A resistivity of 7.97×10 −4  Ω cm and an average transmittance of more than 83% in the 400–1100 nm range were obtained with an optimal H2 flow rate of 1.2 sccm. Results of theoretical calculations show that the H dopant behaves as a shallow donor in the TZO films. The doping position of H is located in a BC ⊥ configuration at the center of the Zn-O bond, in which the O atom bonded to a substituted Ti atom parallel to the c axis. The charge carrier bands shifted from Ti 3d and O 2p orbitals in the TZO film to Ti 3d and H 1 s orbitals in H and Ti co-doped ZnO films.